Telemonitoring of Active Inflammatory Bowel Disease Using the App TECCU: Short-Term Results of a Multicenter Trial of GETECCU - Mariam Aguas; Javier Del Hoyo; Raquel Vicente; Manuel Barreiro-de Acosta; Luigi Melcarne; Alejandro Hernandez-Camba; Lucía Madero; María Teresa Arroyo; Beatriz Sicilia; María Chaparro; María Dolores Martin-Arranz; Ramón Pajares; et al. (JMIR Publications, 2024)
BackgroundTelemonitoring for inflammatory bowel disease (IBD) has not consistently demonstrated superiority over standard care; however, noninferiority may be an acceptable outcome if remote care proves to be more efficient. ObjectiveThis study aims to compare the remission time and quality of life of patients with active IBD managed through standard care versus the TECCU (Telemonitoring of Crohn Disease and Ulcerative Colitis) app. MethodsA 2-arm, randomized, multicenter trial with a noninferiority design was conducted across 24 hospitals in Spain. The study included adult patients with IBD who were starting immunosuppressive or biological therapy. Participants were randomized into 2 groups: the telemonitoring group (G_TECCU) and the standard care group (G_Control). The follow-up schedule for the telemonitoring group (G_TECCU) was based on contacts via the TECCU app, while the control group (G_Control) adhered to standard clinical practice, which included in-person visits and telephone calls. In both groups, treatment adjustments were made based on the progression of disease activity and medication adherence, assessed using specific indices and biological markers at each check-up. The primary outcome was the duration of remission after 12 weeks, while secondary outcomes included quality of life, medication adherence, adverse events, and patient satisfaction. ResultsOf the 169 patients enrolled, 158 were randomized and 150 were analyzed per protocol: telemonitoring (n=71) and control (n=79). After 12 weeks, the time in clinical remission was not inferior in the telemonitoring group (mean 4.20, SD 3.73 weeks) compared with the control group (mean 4.32, SD 3.28 weeks), with a mean difference between arms of -0.12 weeks (95% CI -1.25 to 1.01; noninferiority P=.02). The mean reduction in C-reactive protein values was -15.40 mg/L (SD 90.15 mg/L; P=.19) in the G_TECCU group and -13.16 mg/L (SD 54.61 mg/L; P=.05) in the G_Control group, with no significant differences between the 2 arms (P=.73). Similarly, the mean improvement in fecal calprotectin levels was 832.3 mg/L (SD 1825.0 mg/L; P=.003) in the G_TECCU group and 1073.5 mg/L (SD 3105.7 mg/L; P=.03) in the G_Control group; however, the differences were not statistically significant (P=.96). Quality of life improved in both groups, with a mean increase in the 9-item Inflammatory Bowel Disease Questionnaire score of 13.44 points (SD 19.1 points; P<.001) in the G_TECCU group and 18.23 points (SD 22.9 points; P=.001) in the G_Control group. Additionally, the proportion of patients who adhered to their medication significantly increased from 35% (25/71) to 68% (48/71) in the G_TECCU group (P=.001) and from 46% (36/79) to 73% (58/79) in the G_Control group (P=.001). The satisfaction rate remained stable at around 90%, although noninferiority was not demonstrated for the secondary outcomes. ConclusionsTelemonitoring patients with active IBD is not inferior to standard care for achieving and maintaining short-term remission. The TECCU app may serve as a viable alternative follow-up tool, pending confirmation of improved health outcomes and cost-effectiveness over the long-term. Trial RegistrationClinicalTrials.gov NCT06031038; https://clinicaltrials.gov/ct2/show/NCT06031038 International Registered Report Identifier (IRRID)RR2-10.2196/resprot.9639